Doprowadź do wyrażenia do najprostszej postaci:
a)x(y+z)-5(x-4xz-xy)+5x
b)6x(2x⁴+3x³-4x²-2x)-3x²(x³+6x²+6x)+30x³
c)7(1-y)-7[2x²-5xy²-6x(x²-2y²)]+14x²(1-3x)
Prosze O szybkie rozwiązanie :)



Odpowiedź :

a) x(y+z) - 5(x-4xz-xy) + 5x = xy + xz - 5x + 20 xz + 5xy + 5x =6xy + 21xz
b) 6x(2x⁴+3x³-4x²-2x)-3x²(x³+6x²+6x)+30x³ =
=12x do piątej + 18x⁴ -24x³ -12x² - 3x do piatej - 18x³ + 30x³ =
=9x do piątej -12x³ - 12x²
c) 7(1-y) - 7[2x² - 5xy² -6x(x²-2y²)] + 14x²(1-3x)=
=7-7y - 7(2x²-5xy² - 6x³ + 12xy²) + 14x² - 42x³=
=7-7y-14x²+35xy² + 42x³ -84xy² + 14x²-42x³ = 49 xy² + 7 -7y
a)xy+xz-5x+20xz+5xy+5x=6xy+21xz
b)12xdo5+18xdo4-24xdo3-12xdo2-3xdo5-18xdo4-18xdo3+30xdo3=9xdo5-12xdo3-12xdo2
c)7-7y-49xydo2